Protect stored cowpeas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Cowpea (Vigna unguiculata) is cultivated widely in Africa and its centre of production is Nigeria. A good source of vegetable protein, in certain regions cowpea provides people with nearly 60% of their protein intake. Local farmers often store...